Introducing the families of Wasit Scientific City In the Abbasid era 132-656 AH - Hussain Ali Al-Suwaiti, Muhammad; شهاب علي الجعيفري حمزة (Journal of College of Education, 2022)
The This study dealt with the famous families in the city of Wasit at the end of the Abbasid era, with a touch on some of the media of these families and their contributions in various fields of science and knowledge such as history, philosophy, art, medicine and other Islamic sciences. Wasit distinguished during that era. and we were keen to include everything related to those nights in Islamic sources and modern references.